Clinical and treatment-related determinants of subjective quality of life in patients with first-episode psychosis. (March 2017) - Kwong, Vivian Wing Yan; Chang, Wing Chung; Chan, Gloria Hoi Kei; Jim, Olivia Tsz Ting; Lau, Emily Sin Kei; Hui, Christy Lai Ming; Chan, Sherry Kit Wa; Lee, Edwin Ho Ming; Chen, Eric Yu Hai
Abstract: Subjective quality of life (SQoL) has been increasingly studied in first-episode psychosis (FEP). Prior research primarily examined the impact of psychiatric symptoms on SQoL. Relationship between treatment-related factors and SQoL is under-studied. In this study, 159 Chinese patients who had completed 2-year treatment from early intervention service in Hong Kong were recruited. Assessments on premorbid adjustment, clinical profiles including social anxiety measure, functioning, antipsychotic-induced extrapyramidal side-effects and attitude toward medication treatment were conducted. SQoL was evaluated by Chinese version SF36 which generated mental and physical component summary (MCS and PCS) scores for analysis. Our results showed that more severe positive symptoms, higher level of depression, greater social anxiety, more negative attitude toward antipsychotic medications and greater degree of akathisia independently predicted lower MCS score. Higher social anxiety level and poorer functioning predicted lower PCS score. Our results indicate that affective and positive symptoms, functioning, and treatment-related variables are critical determinants of SQoL in FEP patients. These identified factors thus represent potentially malleable therapeutic targets for early detection and prompt intervention to promote enhancement of SQoL in the early stage of illness. Highlights: The study aimed to identify determinants of subjective quality of life (SQoL) in Chinese first-episode psychosis patients. Positive symptoms, depression, social anxiety, akathisia and negative treatment attitude predict poorer mental health SQoL. Social anxiety and lower functional levels predict poorer physical health SQoL.